2017
DOI: 10.1016/j.marchem.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The drivers of biogeochemistry in beach ecosystems: A cross-shore transect from the dunes to the low-water line

Abstract: This study addresses key processes in high-energy beach systems using an interdisciplinary approach. We assess spatial variations in subsurface pore water residence times, salinity, organic matter (OM) availability, and redox conditions and their effects on nutrient cycles as well as on microbial community patterns and microphytobenthos growth. At the study site on Spiekeroog Island, southern North Sea, beach hydrology is characterized by the classical zonation with an upper saline plume (USP), a saltwater wed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
164
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(180 citation statements)
references
References 106 publications
14
164
2
Order By: Relevance
“…The western part of the island is underlain by a freshwater lens (Figure b), which is confined by clay layer at about 40 m below NHN (standard elevation zero) and exhibits water ages up to 51 years (Röper et al, ; Seibert et al, ). Due to varying flow paths, fresh groundwater of various ages is delivered to the intertidal subsurface (Beck et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The western part of the island is underlain by a freshwater lens (Figure b), which is confined by clay layer at about 40 m below NHN (standard elevation zero) and exhibits water ages up to 51 years (Röper et al, ; Seibert et al, ). Due to varying flow paths, fresh groundwater of various ages is delivered to the intertidal subsurface (Beck et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study focuses on redox constituents in sediments influenced by mesotidal conditions at a high energy beach on Spiekeroog Island, Germany, located in the southern North Sea. Previous work at this site has indicated that the whole span of organic matter degradation pathways occurs, from aerobic respiration to sulfate reduction (Beck et al, ; Reckhardt et al, ; Waska et al, ).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Detailed molecular characterization of dissolved organic matter on samples from the Northern Germany Wadden Sea suggested the release of labile marine DOC and other nutrients from buried algal and microbial biomass, which were preferentially consumed relative to DOC of terrestrial origin (Seidel et al, ). Dissolved organic matter composition of intertidal sands also showed significant correlation to the supplied marine and terrestrial organic matter, while organic matter composition in tidal flats were decoupled from seasonality and more related to early diagenetic processes (Beck et al, ; Seidel et al, ). These studies collectively indicate that organic matter dynamics within sediments are influenced by both hydrologic transport and diagenesis and call for further work that comprehensively integrate the roles of particulate and dissolved carbon dynamics in beach systems.…”
Section: Introductionmentioning
confidence: 99%